Improved chemical water oxidation with Zn in the tetrahedral site of spinel-type ZnCo2O4 nanostructure - Chakraborty, Biswarup; Indra, Arindam; Menezes, P. V.; Drieß, Matthias; Prashanth W., Menezes (Elsevier Ltd., 2020)
Spinel oxides with the composition of AIIBIII 2O4 (A and B are metal ions) represent an important class of anode material for water splitting to replace the currently used noble-metal catalysts. Although spinel electrocatalysts have widely been investigated for electrochemical water oxidation, the role of octahedral and tetrahedral sites influencing catalytic performance has been a topic of discussion for a long time and still under debate. Lately, this issue has been addressed by substituting redox-inert cation to the tetrahedral sites of cobalt spinels and comparing the electrochemical activity between them. However, rapid surface structural transformation of the catalysts under operating electrochemical conditions makes it difficult to infer the exact contribution of tetrahedral and octahedral sites for water oxidation. Herein, for the first time, we utilize the oxidant-driven water oxidation approach to reveal the responsible active sites using two spinel-type nanostructures, ZnIICo2 IIIO4 and CoIICo2 IIIO4 (Co3O4), synthesized by using a single-source precursor approach. Strikingly, a superior O2 production rate (0.98 mmolO2 molCo −1 s−1) following first-order reaction kinetics was achieved for ZnCo2O4 in the presence of CeIV as sacrificial electron acceptor compared to Co3O4 spinel (0.29 mmolO2 molCo −1 s−1). The structural and morphological stability of the ZnCo2O4 and Co3O4 post water oxidation catalysis confirms that the catalytic activity is strictly controlled by the geometry and electronic structure of the active site of the spinel structure. The higher performance of ZnCo2O4 over Co3O4 further indicates that the presence of CoII is not essential for catalytic water oxidation. The presence of redox inert ZnII at the tetrahedral site of ZnCo2O4 can facilitate the stabilization of a high-valent CoIV intermediate via oxidation of CoIII (situated at the octahedral site), and this intermediate can be regarded as the active species for water oxidation catalyst along with structural defects caused by surface Zn leaching. © 2019 Elsevier Ltd
Keywords: Chemical water-oxidation; Spinel-type structure; Sustainable catalyst; Tetrahedral versus octahedral site; ZnCo2O4 nanochains